2022
DOI: 10.1007/s00018-022-04440-w
|View full text |Cite
|
Sign up to set email alerts
|

A stable cyclized antimicrobial peptide derived from LL-37 with host immunomodulatory effects and activity against uropathogens

Abstract: The increasing antibiotic resistance among uropathogenic bacteria warrants alternative therapeutic strategies. We demonstrate the potential of the synthetic peptide CD4-PP, designed by dimerization and backbone cyclization of the shortest antimicrobial region of human cathelicidin, LL-37. CD4-PP is active against clinical and type strains of common uropathogens Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa at concentrations substantially below cellular cytotoxic levels and induced membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…The peptide induced the formation of blebs and ruffling of the bacterial surface compared with controls (Figure A–F). The blebbing pattern was comparable with what we had previously observed for E. coli . This suggests that CD4-PP has similar bacterial membrane deformation potential against both Gram-negative and Gram-positive bacteria.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The peptide induced the formation of blebs and ruffling of the bacterial surface compared with controls (Figure A–F). The blebbing pattern was comparable with what we had previously observed for E. coli . This suggests that CD4-PP has similar bacterial membrane deformation potential against both Gram-negative and Gram-positive bacteria.…”
supporting
confidence: 88%
“…CD4-PP was designed as a backbone cyclic dimer peptide based on the shortest antimicrobial sequence of LL-37, , called KR-12 . Two KR-12 units were then connected using linkers of four amino acids into a seamless chain of peptide bonds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 White et al reported that an improved form of the cyclic KR-12 peptide shows promising results as a new antibiofilm agent. 38 In all these studies, peptide engineering to enhance peptide stability was an important part of the research. How peptide stability might influence the experimental outcomes is not well understood.…”
Section: ■ Discussionmentioning
confidence: 99%
“…C10-KR8d, made in d -amino acids, is highly selective and potent . White et al reported that an improved form of the cyclic KR-12 peptide shows promising results as a new antibiofilm agent . In all these studies, peptide engineering to enhance peptide stability was an important part of the research.…”
Section: Discussionmentioning
confidence: 99%